Investigation of Autonomic Involvement with Facial Sympathetic Skin Response in Patients with Idiopathic Cervical Dystonia - Nur Turkmen; Muhammed Yildirim; Ebru Bilge Dirik; Sule Bilen (Neurological Sciences and Neurophysiology)
Objective: The objective of this study was to examine the sympathetic skin response (SSR) as an electrophysiologic indicator of dysfunction in the sympathetic nervous system among patients with idiopathic cervical dystonia (ICD) and compare the findings with a healthy control group. Furthermore, to identify differences in SSR responses between the facial and extremity regions and determine a disease-specific cutoff value, if present. Methods: SSR recordings were taken from the face, hands, and feet of 30 patients with ICD and 33 healthy volunteers. Autonomic dysfunction was assessed using the composite autonomic symptom score-31 (Compass-31). SSR parameters, including mean amplitudes and latencies, were analyzed, and cutoff values distinguishing patients from healthy individuals were identified. Results: Patients with ICD had significantly higher Compass-31 scores (mean ≥8, P < 0.05) compared with controls. Facial SSR (F-SSR) amplitudes were notably lower in patients with ICD, with a cutoff value of 390 μV (area under the curve 95% confidence interval, P = 0.031). However, other SSR parameters, such as extremity amplitudes and latencies, showed no significant differences. Although SSR absence was more frequent in patients with ICD, this difference was not statistically significant. Additionally, the relationship between botulinum toxin dose and facial SSR amplitudes was found to be dose-independent, further supporting the absence of a dose-dependent effect on sudomotor function. Conclusion: Patients with ICD showed clinical and electrophysiologic evidence of sympathetic dysfunction, as assessed using Compass-31 and SSR, respectively. F-SSR amplitudes emerged as a noninvasive and objective marker of autonomic dysfunction in ICD, demonstrating diagnostic potential that surpasses extremity-based SSR recordings.